2011
DOI: 10.1093/jxb/erq393
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the three genes encoding 1-deoxy-D-xylulose 5-phosphate synthase in maize

Abstract: The 1-deoxy-D-xylulose 5-phosphate synthase (DXS) enzyme catalyses the first biosynthetic step of the 2-C-methyl-D-erythritol 4-phosphate (MEP) pathway. In plants the MEP pathway is involved in the synthesis of the common precursors to the plastidic isoprenoids, isopentenyl diphosphate and dimethylallyl diphosphate, in plastids. DXS is recognized as limiting this pathway and is a potential target for manipulation to increase various isoprenoids such as carotenoids. In Zea mays three dxs genes exist that encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
98
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(108 citation statements)
references
References 70 publications
9
98
1
Order By: Relevance
“…S5; Walter et al, 2002;Phillips et al, 2007). Some plant species have a third DXS protein cluster referred to as the DXS3 clade, which has been proposed to participate in the synthesis of some products essential for plant survival (Cordoba et al, 2009(Cordoba et al, , 2011. We found that SrDXS3 was a member of the DXS3 clade (Fig.…”
Section: Expression and Molecular Analysis Of The Mep Pathway And Idimentioning
confidence: 75%
“…S5; Walter et al, 2002;Phillips et al, 2007). Some plant species have a third DXS protein cluster referred to as the DXS3 clade, which has been proposed to participate in the synthesis of some products essential for plant survival (Cordoba et al, 2009(Cordoba et al, , 2011. We found that SrDXS3 was a member of the DXS3 clade (Fig.…”
Section: Expression and Molecular Analysis Of The Mep Pathway And Idimentioning
confidence: 75%
“…DXS1 is a limiting factor in upregulation of the carotenoid pathway in A. thaliana 49 . DXS1 expression is induced by light 50,51 , and it is the main DXS isoform catalyzing the biosynthesis of isoprenoid and carotenoid precursors in photosynthetic metabolism 52,53 . DXS1 also regulates carotenoid accumulation in A. thaliana and tomato 54,55 .…”
Section: A Model For Carotenoid Accumulation In Carrot Rootsmentioning
confidence: 99%
“…5:1 mixture of IPP and DMAPP (Figure 1). Unlike Arabidopsis, most plants appear to have small gene families encoding DXS isoforms of at least two classes (Walter et al, 2002;Krushkal et al, 2003;Kim et al, 2005;Cordoba et al, 2009;Paetzold et al, 2010;Cordoba et al, 2011). All classes of DXS isozymes have been found to participate in carotenoid biosynthesis.…”
Section: Mep Pathway To Ggppmentioning
confidence: 99%